Computer science : an overview. - Brookshear, J. Glenn, 1944- (Boston : Addison-Wesley, 2003)
Samenvatting:This classic book provides an overview to the field of computing, withnew material on networking, C#, XML, and Java, making it the most currentbook available. The seventh edition has been thoroughly updated todiscuss important trends in such areas as networking and the Internet,software engineering, public-key encryption, and artificial intelligence.The discussions of the ethical and legal issues revolving aroundcomputing have been expanded in this edition. This book is for those whoare interested in taking a tour of the field of computer science, as wellas those taking an introductory course on these topics.
Keywords: Computers; Informatica